The Islamic Islamic Religious Education Learning System - Fajrul Munir Fairuz (Ilomata International Journal of Social Science, 2020)
Islamic religious learning system through the CTL Contextual Teaching and Learning model in improving the thinking ability of madrasah students in Islamic boarding schools. Islamic religious education in madrasah includes (al-Qur'an-Hadits, Morality, Jurisprudence, and Cultural History of Islam). Learning Islamic religious education often uses lecture methods so students feel bored and even disparage when studying their Islamic Education while doing other activities. The author is interested in choosing this topic because no one has researched with the same title. The benefits of this research are expected to help teachers, especially those who teach Islamic education in madrasah. The reason other researchers are not interested in this title is that they think the CTL method cannot be used to improve the quality of learning, especially PAI in madrash. While in this study the authors tried to find direct effects, especially CTL can improve students' thinking skills in madrasah. The research method uses a qualitative approach and study documentation. Data processing in using the critical-analytical method, which is analyzing and interpreting data. The author is interested in researching with the title above because he wants to prove that the Islamic religious learning system through the CTL model can improve the thinking ability of madrasa students. The research findings are the Islamic religious education learning system through CTL, a learning approach that emphasizes the process of full involvement of students to be able to find the material being studied and relate it to real life situations and conditions. Research conclusions: Implementation of Islamic religious education learning system through the CTL model in improving the thinking ability of Islamic boarding school students through stages of constructivism (constructionvism), Inquiry (finding), Questioning (asking), Learning Community (learning community), Modeling (modeling), Reflection (reflection), and Authentic Assessment (actual assessment). Implications of research, students' thinking ability will increase because they are given the freedom to explore their learning. So the Islamic religious education learning system through the CTL model can improve students' thinking abilities and enthusiasm of students to continue learning and discover for themselves (material/concepts) what they learn.